ANALISIS KONSEP PERASAAN DAN EMOSI DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Fadilatul Fauziah; M. Khoiruddin; Ahmad Ali Wafi; Arini Hidayati; Titin Nurhidayati (PT. Hasba Edukasi Mandiri, 2026)
This article stems from a phenomenon in the field of education, where most educators and parents tend to overlook the psychological aspects of student learning. In fact, education should not only focus on intellectual and physical intelligence, but also on developing students’ psychological aspects to ensure optimal learning. This research focuses on analyzing and revealing the concepts of feelings and emotions in relation to learning, the concepts of feelings and emotions from the perspective of Islamic education, as well as their relevance to Islamic education learning. This study uses a qualitative research method with a library research approach. The findings of the study conclude several key points. First, the psychology of feelings and emotions plays a fundamental role in the learning process because both directly influence students’ motivation, attention, social interaction, academic success, and reallife performance. Second, the psychological concepts of feelings and emotions align with the concept of al-Nafs in Islamic educational psychology, referring to the soul's phenomena as a spiritual component of the human inner self. Third, the concepts of feelings and emotions are relevant to the learning process in Islamic education, which seeks to develop these two components to shape a holistic Muslim generation. Ultimately, educators need to place greater emphasis on these psychological components and foster their positive development through comprehensive teaching and guidance to achieve the goals of Islamic education.